UJI ANTIMITOSIS EKSTRAK ETANOLIK KLIKA SIRSAK (Annona muricata L.) TERHADAP SEL TELUR LANDAK LAUT (Tripneustes gratilla L.) TERFERTILISASI - Niken Pratiwi Liambo; Abd. Malik; Aktsar Roskiana Ahmad (Jurnal Fitofarmaka Indonesia, 2016)
Soursop belongs to Annonaceae family. In the traditional medicine has been as anticancer, antivirus, wound healing, lowering uric acid levels. This study aims to determine the IC80value extract ethanolic of soursop bark to sea urchin egg (Tripneustes gratilla L.) fertilized. Dryed sample extracted by maceration method using ethanol solvent. Retrieved rendamen extract as much as 2,525 %. Based on qualitative test chemical components that extract ethanolic of soursop bark contain   tannins, saponins, alkaloids and flavonoids. Antimitotic test conducted on extract ethanolic of soursop bark (A.muricata) obtained by looking at the sea urchin egg cell inhibition (Tripneustes gratilla L.) to calculate IC80 values by probit analysis method. Antimitotic test results showed that the extract ethanolic of soursop bark (A.muricata) as an antimitotic active with IC80 values of 1,56 x 10-3 mg/ml. Although the potential is lower than that of vincristine inhibit 80 % of eggs fertilized with Tripneustes gratilla L. IC80value is 7,046 x 10-7 mg/ml.